KADAR KOLESTEROL TELUR PUYUH SETELAH PEMBERIAN TEPUNG KUNYIT DALAM PAKAN - Aviati, Vina; Mardiati, Siti Muflichatun; Saraswati, Tyas Rini (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2014)
The quail egg have complete nutrient content but its cholesterol level higher than chicken egg. This research was design to study the effect of turmeric powder supplementation to decline the cholesterol level of the quail egg. This experiment was designed by using the completely randomized design (CRD). The experimental animals were 45 female quails and   divided in to 3 groups, with 5 replications; there were P0 : as control, the group of the quail that given a standart concentrate,   P1 : the group of the quail with 54 mg/quail/day turmeric powder supplementation  before sexual maturity (from 14 days old during 1 month), and P2 : the group of quail with 54 mg/quail/day turmeric powder supplementation when sexual maturity onset (from 45 days old during 1 month). The cholesterol level of the egg sample of the quail at production in 4th month and its feed intake from each experimental group was analyzed by using analysis of variance (ANOVA) and followed by Duncan test. The result of this research showed that giving turmeric powder does not influence the feed intake and the cholesterol level of the quail egg which was given a treatment before sexual maturity, but that influence to increase the cholesterol level of quail egg that given turmeric powder when sexual maturity onset. It concluded that turmeric powder supplementation in food  not effective to decrease the cholesterol level of quail egg.